Concrete Durability : Cementitious Materials and Reinforced Concrete Properties, Behavior and Corrosion Resistance - Rendon Diaz Miron, Luis Emilio; Koleva, Dessi A. (Springer International Publishing : Imprint: Springer, 2017)
This book describes the newest developments in the creation of concrete using smart additives and supplementary cementitious materials as well as methods, technology and novel admixtures to monitor, evaluate and control steel corrosion in reinforced concrete. Industry experts and research specialists explain the structural, physical, and chemical properties of various types of concrete and its applications. They detail the characteristics preferred for manufacturing specific types of concrete. The book chapters also focus on the electrochemical state of the steel reinforcement in view of steel corrosion and corrosion control. The book encompasses main aspects as follows: Characterizes supplementary cementitious materials used for making concrete; Details the properties of concrete and the components, essential for concrete manufacturing including Portland cement, calcium sulfate, fly ash, and cupola slag; Explains the necessary treatments for the preparation of concrete during the manufacturing process. Describes the major durability-related challenge for reinforced concrete structures i.e. chloride-induced steel corrosion, in view of sensors and sensor technology for early corrosion detection. Defines stray-current induced corrosion and the consequences for both steel and concrete bulk matrix. Illustrates the potential of hybrid nano-materials to affect both steel and concrete, targeting corrosion control and superior performance of reinforced concrete structures. Targets dissemination of fundamentally substantiated mechanisms and verification of innovative applications, in view of bringing confidence for industrial utilization of novel solutions or practices in civil engineering.
Keywords: Materials science.; Chemical engineering.; Building materials.; Structural materials.; elektronické knihy; electronic books